Tax differences and foreign direct investment in the EU27 - Åsa Hansson; Karin Olofsdotter (Lund University, School of Economics and Management, Department of Economics, 2010)
We empirically analyze the impact of corporate tax rates and agglomeration economies on FDI using panel data on bilateral FDI flows and stocks in the enlarged European Union. The novelty of the paper is that it explicitly deals with agglomeration forces and how these may explain differences in tax policies between new and old member countries. The empirical analysis closely follows the implicit underlying model where the foreign direct investment decision is seen as a two-step procedure that entails: 1) whether or not to invest; and 2) the amount of FDI to invest. Using recent data on corporate tax rates for all 27 EU member countries from 1995-2006, we find that there are large differences in the determinants of FDI going to the EU15 and new member countries. While tax differentials mainly seem to influence FDI flows to new members, agglomeration economies appear to play a somewhat more important role for the amount of investment made within the EU15. In addition, significant differences are found between the determinants of the extensive and intensive margins of the FDI decision.
Keywords: F12; F15; F21; H71; 330; Corporate taxes; agglomeration economies; foreign direct investment